The combined effect of sleep and time of day on emotion decoding from dynamic visual cues in older adults - Tsokanaki P; Moraitou D; Papantoniou G (Neuropsychiatric Disease and Treatment)
Paraskevi Tsokanaki,1 Despina Moraitou,1 Georgia Papantoniou2 1Section of Cognitive and Experimental Psychology, School of Psychology, Aristotle University of Thessaloniki, Thessaloniki, 2Department of Early Childhood Education, University of Ioannina, Ioannina, Greece Abstract: It is well known that night sleep is a decisive factor for the effective functioning of the human body and mind. In addition to the role of sleep, older adults report that they are “morning types” and that their cognitive and emotional abilities seem to be at a higher level in the morning hours. In this vein, this study is aimed at examining the effect of sleep combined with the “time of day” condition on a specific ability that is crucial for interpersonal communication, namely, emotion recognition, in older adults. Specifically, the study compared older adults’ performance in decoding emotions from ecologically valid, dynamic visual cues, in two conditions: “early in the morning and after night sleep”, and “in the afternoon and after many hours since night sleep”. An emotion recognition task was administered twice to 37 community-dwelling older adults. The results showed a statistically significant higher performance in the morning in decoding all emotions presented, compared to the afternoon condition. Pleasant surprise, sadness, and anxiety were revealed as the most difficult emotions to be recognized in the afternoon condition. Keywords: aging, cognition, emotion recognition